Direcionadores para implantação da saúde baseada em valor em instituições hospitalares - Silva, Flávia Luana da (Universidade do Vale do Rio dos Sinos, 2021)
Health services have faced a worldwide challenge over the years in terms of raising the quality of their care and lowering costs. Challenges such as technology, population aging, new diseases, and the greater active perception of the patient lead institutions to reinvent themselves in their management. The old health systems are no longer sufficient to meet population needs, which drives a trend towards the adoption of value-based health with a central focus on the patient. Value-based healthcare still presents challenges for its implementation, given that, the objective of this work is to propose a model with the guidelines that healthcare institutions need to have for the implementation of value-based healthcare. The working method adopted to conduct this research was Design Science Research, addressing six phases of the method related to the specific objectives of the research. The research has a qualitative approach, in which the systematic literature review was the main technique of data collection. In the systematic literature review, research with specific applications of drivers was observed, and with the understanding of the results achieved by the authors, the drivers were selected to complement each other in implantation. A theoretical survey covering all the drivers was developed with its basic applications. The model was built presenting the necessary drivers for implementation, focusing its structure on the basic elements of health based on value, quality, and cost. The TDABC costing method and the DRG were identified as cost drivers. In terms of quality, the drivers complement each other in their deliveries, these being ICHOM, PREMs, PROMs, and QALY. The model’s contribution is to indicate the necessary drivers for the implementation of value-based health, serving as a theoretical basis for further application. With the main concepts and applications, it contributes to the foundation in the face of implantation interest. In this way, the contributions can be in the scientific context in which it promotes a new vision of the union of results of specific elements for a common objective and in the practical context, in which its complete application can measure the value delivered to the patient, and in this way bring a new perspective of management and culture in a health institution.
Keywords: Saúde baseada em valor; Qualidade; Custos; Direcionadores; Value-based healthcare; Quality; Cost; Guidelines; ACCNPQ::Engenharias::Engenharia de Produção